1997
DOI: 10.1136/jnnp.63.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Extracranial and intracranial vertebrobasilar dissections: diagnosis and prognosis

Abstract: Objectives-To compare the diagnosis and prognosis of extracranial versus intracranial vertebral artery dissections without intracerebral haemorrhage. Methods-Twenty two vertebral artery dissections were defined by intra-arterial angiography and classified in two groups: group 1, nine extracranial dissections (seven patients) and group 2, 13 intracranial dissections (nine patients), involving the basilar artery in five cases. Bilateral dissections were found in 38% of the population. Before angiography, all the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
121
1
10

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(140 citation statements)
references
References 22 publications
8
121
1
10
Order By: Relevance
“…7,22,26 In our present study, 3 patients showed Ն2 attacks with neurological deficit within 1 month to 12 years, and some patients complained of repeated symptoms, such as vertigo and headache. These attacks and repeated symptoms may have resulted from the aforementioned dynamic condition of vertebrobasilar artery dissection; however, it is possible that they were due to recurrent arterial dissection.…”
Section: Treatment and Outcomementioning
confidence: 94%
See 1 more Smart Citation
“…7,22,26 In our present study, 3 patients showed Ն2 attacks with neurological deficit within 1 month to 12 years, and some patients complained of repeated symptoms, such as vertigo and headache. These attacks and repeated symptoms may have resulted from the aforementioned dynamic condition of vertebrobasilar artery dissection; however, it is possible that they were due to recurrent arterial dissection.…”
Section: Treatment and Outcomementioning
confidence: 94%
“…Some recent studies indicate the possibility of establishing the diagnosis of extracranial arterial dissection with the use of ultrasound, 26 helical CT, 27 and MR angiography. 14,15 However, the ultrasound technique does not have diagnostic value for intracranial arteries, and helical CT is also less reliable for detecting abnormality in the posterior fossa because of many artifacts.…”
Section: Vascular Imagingmentioning
confidence: 99%
“…10 The use of ultrasonographic techniques in the initial assessment of patients with suspected dissection has invariably required confirmatory testing with additional angiography, either invasively or noninvasively. The technique is dependent on the accessibility of the region to screening and although helpful for proximal dissections, the detection of more distal disease is limited 11,12 Controversy continues as to the optimal management of patients with asymptomatic vertebral artery injury. Guidelines published in 2002 indicated that there was insufficient evidence to support anticoagulation in asymptomatic patients, specifically relating to a 14% risk of complications from anticoagulant use.…”
Section: Discussionmentioning
confidence: 99%
“…CT angiography and MRA appear to have similar specificities and sensitivities; however, MRA allows both luminal narrowing and thrombus to be seen in addition to the characteristic appearances such as 'string sign', pseudoaneurysm, double lumen or an intimal flap. 11,12 The preferred imaging techniques for a thoracic aortic dissection in the acute setting are spiral CT, transoesophageal echocardiography (TOE), MRI or conventional CT for haemodynamically stable patients. TOE is less sensitive and specific than spiral CT or MRI, and TOE is operator-dependent.…”
Section: Diagnosismentioning
confidence: 99%